The identification of (ETV6)/RUNX1-regulated genes in lymphopoiesis using histone deacetylase inhibitors in ETV6/RUNX1-positive lymphoid leukemic cells - Starkova, Julia; Madzo, Jozef; Cario, Gunnar; Kalina, Tomas; Ford, Anthony; Zaliova, Marketa; Hrusak, Ondrej; Trka, Jan (Clinical cancer research, 2007)
PURPOSE: Chimeric transcription factor ETV6/RUNX1 (TEL/AML1) is believed to cause pathologic block in lymphoid cell development via interaction with corepressor complex and histone deacetylase. We wanted to show the regulatory effect of ETV6/RUNX1 and its reversibility by histone deacetylase inhibitors (HDACi), as well as to identify potential ETV6/RUNX1-regulated genes. EXPERIMENTAL DESIGN: We used luciferase assay to show the interaction of ETV6/RUNX1 protein, ETV6/RUNX1-regulated gene, and HDACi. To identify ETV6/RUNX1-regulated genes, we used expression profiling and HDACi in lymphoid cells. Next, using the flow cytometry and quantitative reverse transcription-PCR, we measured differentiation changes in gene and protein expression after HDACi treatment. RESULTS: Luciferase assay showed repression of granzyme B expression by ETV6/RUNX1 protein and the reversibility of this effect by HDACi. Proving this regulatory role of ETV6/RUNX1, we identified, using complex statistical analysis, 25 genes that are potentially regulated by ETV6/RUNX1 protein. In four selected genes with known role in the cell cycle regulation (JunD, ACK1, PDGFRB, and TCF4), we confirmed expression changes after HDACi by quantitative analysis. After HDACi treatment, ETV6/RUNX1-positive cells showed immunophenotype changes resembling differentiation process compared with other leukemic cells (BCR/ABL, ETV6/PDGFRB positive). Moreover, ETV6/RUNX1-positive leukemic cells accumulated in G(1)-G(0) phase after HDACi whereas other B-lineage leukemic cell lines showed rather unspecific changes including induction of apoptosis and decreased proliferation. CONCLUSIONS: Presented data support the hypothesis that HDACi affect ETV6/RUNX1-positive cells via direct interaction with ETV6/RUNX1 protein and that treatment with HDACi may release aberrant transcription activity caused by ETV6/RUNX1 chimeric transcription factor.
Keywords: Tumor Cells, Cultured; represorové proteiny; protoonkogenní proteiny c-ets; Lymphopoiesis; Reverse Transcriptase Polymerase Chain Reaction; Cell Proliferation; Humans; Histone Deacetylase Inhibitors; granzymy; Repressor Proteins; Proto-Oncogene Proteins c-ets; apoptóza; Granzymes; proliferace buněk; inhibitory histondeacetylas; polymerázová řetězová reakce s reverzní transkripcí; nádorové buňky kultivované; Core Binding Factor Alpha 2 Subunit; ETS Translocation Variant 6 Protein; Leukemia, Lymphoid; lymfoidní leukemie; stanovení celkové genové exprese; Gene Expression Regulation, Leukemic; lidé; Gene Expression Profiling; lymfopoéza; protein ETS, translokační varianta 6; protein PEBP2A2; Apoptosis; regulace genové exprese u leukemie